Differential kinematics of contemporary industrial robots - Szkodny, Tadeusz (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents a simple method of avoiding singular configurations of contemporary industrial robot manipulators of such renowned companies as ABB, Fanuc, Mitsubishi, Adept, Kawasaki, COMAU and KUKA. To determine the singular configurations of these manipulators a global form of description of the end-effector kinematics was prepared, relative to the other links. On the basis of this description , the formula for the Jacobian was defined in the end-effector coordinates.
Keywords: kinematics; manipulators; mechanical system; robot kinematics